2014
DOI: 10.3389/fpsyg.2014.01234
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of uncorrected visual acuity and contrast sensitivity with perceptual learning and transcranial random noise stimulation in individuals with mild myopia

Abstract: Perceptual learning has been shown to produce an improvement of visual acuity (VA) and contrast sensitivity (CS) both in subjects with amblyopia and refractive defects such as myopia or presbyopia. Transcranial random noise stimulation (tRNS) has proven to be efficacious in accelerating neural plasticity and boosting perceptual learning in healthy participants. In this study, we investigated whether a short behavioral training regime using a contrast detection task combined with online tRNS was as effective in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 50 publications
1
51
0
Order By: Relevance
“…Naturally, in the case of refractive defects, sensory training does not modify the structure of the eye; nonetheless improvements on uncorrected (that is: in absence of any optical correction) VA and contrast sensitivity (CS) using perceptual learning paradigms have been found; the proposed underlying mechanism in the case of non-cortical visual defects is an increase of signal-to-noise ratio of the de-focused retinal image (Durrie & McMinn, 2007;Tan & Fong, 2008). PL with the use of single Gabor stimuli, has been shown to be able to increase VA and CS in a clinical population of patients with amblyopia (Zhou, et al, 2006), and in recent studies conducted by Camilleri, Pavan, Ghin, Battaglini, et al (2014) and Casco et al (2014) it was found that PL using a simple contrast detection task is able to improve uncorrected VA in participants with mild myopia.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Naturally, in the case of refractive defects, sensory training does not modify the structure of the eye; nonetheless improvements on uncorrected (that is: in absence of any optical correction) VA and contrast sensitivity (CS) using perceptual learning paradigms have been found; the proposed underlying mechanism in the case of non-cortical visual defects is an increase of signal-to-noise ratio of the de-focused retinal image (Durrie & McMinn, 2007;Tan & Fong, 2008). PL with the use of single Gabor stimuli, has been shown to be able to increase VA and CS in a clinical population of patients with amblyopia (Zhou, et al, 2006), and in recent studies conducted by Camilleri, Pavan, Ghin, Battaglini, et al (2014) and Casco et al (2014) it was found that PL using a simple contrast detection task is able to improve uncorrected VA in participants with mild myopia.…”
Section: Introductionmentioning
confidence: 99%
“…So far, PL has been shown to be effective in improving, among other dysfunctions, visual abilities in amblyopia (Campana, Camilleri, Pavan, Veronese, & Lo Giudice, 2014;Hussain, Webb, Astle, & McGraw, 2012;Levi & Li, 2009;Li, Young, Hoenig, & Levi, 2005;Polat, 2009;Polat, Ma-Naim, Belkin, & Sagi, 2004;Zhou, et al, 2006), mild refractive defects like myopia (Camilleri, Pavan, Ghin, Battaglini, et al, 2014;Tan & Fong, 2008) and presbyopia (Polat, et al, 2012), and central or peripheral vision loss and cortical blindness (Chung, 2011;Das, Tadin, & Huxlin, 2014;Huxlin, et al, 2009;Kasten, et al, 1998;Plank, et al, 2014;Rosengarth, et al, 2013;Sabel, Kenkel, & Kasten, 2005). In myopia, visual input is limited by an optical de-focus, despite normal neuronal connectivity and image processing.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations